Some Considerations on Plant Types for Dryland Agriculture - Prasad, M V R (Annals of Arid Zone, 2016)
A desired conceptual model or "ideotype" of crop plants like wheat has been developed for irrigated agriculture (Donald, 1968), Such efforts arc yet to yield fruitful results in the case of rainfed crops, more particularly pulses and oilseeds. Plant ideotypes for rainfed agriculture have to be designed so as to achieve a desired and balanced combination of resistance to soil and atmospheric drought on one hand and the plant productivity paramenters on the other. It is necessary that a suitable maturity pattern, that would enable the crop to over come the long spells of drought at critical growth and developmental stages. should be incorporated along with the other factors conducive to a high harvest index aud consistent yielding ability. In order to offer better insurance against crop failure, it is necessary to develop suitable plant types for mixed cropping, taking into consideration various components of competitive ability and complimentarity. Plant breeding and genetical tools such as disruptive selection. mutation breeding, random mating and heterosis breeding would be useful in over coming undesirable character associations in this regard, thus paving way towards desirable gene combinations. Suitable selection procedures, to avoid genetic slippage and exhaustion of variability, have to be practiced.